Diagnostic value of platelet parameters versus interleukin-6 in children with urinary tract infection - Khaled Mahmoud Salem Zayed; Ahmed Mohsen Abdelhakeem; Heba S. Gafar; Tarek Abd El Kareim Eldahshan (SpringerOpen, 2016)
Background: Urinary tract infection (UTI) is a common problem that is frequently encountered by pediatric healthcare providers. Diagnosis of UTI is often difficult, particularly in critically ill patient and in patients with nonspecific and mild symptoms. Testing for platelet parameters is inexpensive, easily accessible and routinely performed that had been recognized as a hallmark in the diagnosis of platelet activation during infection and inflammatory disorders. Aim: To evaluate the value of platelet parameters in the diagnosis of UTI in children in comparison to interleukin-6. Method: This case-control study included 88 children; 44 of them had culture proved UTI. In addition 44 age and sex matched healthy children served as a control group. Complete blood picture with emphasis on platelet parameters (mean platelet volume (MPV), platelet distribution width (PDW) and platelet count), C-reactive protein, erythrocyte sedimentation rate and interleukin-6 serum levels were done for both groups. We investigated the correlation between platelet parameters, inflammatory biomarkers and the type of organism in children with UTI. Results: Platelet parameters were significantly higher in children with UTI in comparison to those of the control group. There was a significant positive correlation between platelet parameters, ESR, CRP and interleukin-6 in children with UTI. MPV & PDW have 90.1% & 88.6% sensitivity and 86.3% & 84.1% specificity respectively for diagnosis of UTI. Platelet parameters are significantly higher in children with gram positive infection. Conclusion: Platelet indices could be used as an indicator of UTI in children. It could predict the type of causative organism. Further researches are needed to evaluate its role for detection of recurrence of UTI in high risk children.